Peranan Insentif Pajak Yang Di Tanggung Pemerintah (DTP) Di Era Pandemi Covid 19 - Lili Marlina; Syahribulan Syahribulan (Economy Deposit Journal (E-DJ), 2020)
The Covid 19 pandemic attack that occurred globally in almost all countries including Indonesia has had a negative impact on the economic sector, especially the MSME business. The government has made various efforts to restore Indonesia's economy, through the Directorate General of Taxes under the authority of the Ministry of Finance has provided tax incentives for taxpayers affected by the Covid 19 pandemic, Final Income Tax Incentives based on Government Regulation Number 23 of 2018. This regulation focuses on Small Business and Intermediate. Taxes that are usually paid by self-deposit or withheld or collected by the Withholder or Collector are 0.5% of gross income, with PMK-44 / PMK.03 / 2020 being borne by the government means that this income is not counted as income subject to tax period tax. April 2020 to December 2020. This research uses descriptive methods, namely through literature studies, literature, which provides an overview of aspects of people's lives that are currently affected by Covid-19. The purpose of providing this tax incentive to MSMEs is to reduce difficulties in meeting operational costs or expense so that MSMEs can survive (Survive) during a pandemic. And efforts to save the national economy and maintain financial system stability have been achieved. As a result, tax incentives and relaxation, providing tax incentives for MSMEs in the business sector can have room to move in the midst of the current Covid 19 pandemic. Socialization to MSME players regarding the existence of this tax incentive, beneficiaries can be productive and able to support the recovery of the national economy, programs and tactical steps are efforts to maintain economic growth but this program is separate, so it is not related to the spread of Covid-19 which can be controlled quickly